iPadagogy in Practice : A Model of m-learning in Elementary Science Education - Cahyandaru, Pramudya; Najib, Khotim Hanifudin; Nofrida, Eka Ridha; Arief, Ardian; Rivalda, Mauriska; Anjarsari, Bernadetha Meilinda (Jurnal PGSD Indonesia, 2025)
This research aims to explore the application of iPad-based mobile learning in learning science in elementary schools through a Systematic Literature Review (SLR) approach. By analyzing various relevant scientific articles, this research identifies how the use of iPads can support the understanding of science concepts, increase learning motivation, and strengthen students' scientific exploration skills. The data analysis process involved a descriptive and thematic approach, where key themes such as the effectiveness of interactive media, increased student engagement, and ease of access to self-directed learning were identified. The results show that iPad-based mobile learning not only facilitates more engaging and interactive learning but also enables students to understand science concepts more deeply through effective visualization and personalized learning experiences. This research makes an important contribution in providing insights for educators in conducting classroom learning.